Incidence and risk factors for cytomegalovirus in kidney transplant patients in Babol, northern Iran - Mostafa Javanian; Arefeh Babazadeh; Farshid Oliaei; Roghayeh Akbari; Abazar Akbarzadepasha; Ali Bijani; Mahmoud Sadeghi (Babol University of Medical Sciences, 2017)
Background: Cytomegalovirus (CMV) disease is an important cause of death and possibly transplant rejection in kidney transplant (KT) patients. This study was conducted to investigate the incidence and risk factors of CMV disease in kidney transplant patients. Methods: All end-stage renal disease (ESRD) patients who underwent kidney transplantation during 1998-2014 and their donors were assessed. All samples were followed-up for approximately 70 months. CMV was identified by polymerase chain reaction (PCR) and/or PP65 antigen in peripheral blood leukocytes along with clinical manifestations. Results: A total of 1450 cases participated in the current study. CMV was diagnosed in 178 out of 725 (24.6%) kidney recipients.  The annual incidence of CMV disease was 4.2%. Patients older than 40 years had a higher incidence of CMV disease. The level of CMV disease incidence in the 41-60 age group was 4 fold compared to those under 20 of age group (P=0.001). Conclusion: This study demonstrated that the incidence of CMV disease in our region is relatively low and also age more than 40 years and EBV infection are the important risk factors in kidney transplant patients. So care and monitoring of these patients are crucial in the first 5 months.